High frequency thin-film bulk acoustic wave resonators for gas- and bio-analytical applications - Ashley, Greg M. (Cranfield University, 2000)
Thin Film Bulk Acoustic Wave Resonators (FBAR) are mechanical micro scale devices that operate in the UHF/Microwave frequency range. This high frequency of operation potentially offers increased sensitivity to the addition of surface mass loading as implied by the famous Sauerbrey equation. FBAR was shown to be responsive to physical and chemical changes in the environment and was further adapted to act as bio-sensor. Thus indicating a universal platform from which to launch an enhanced sensing technology. This thesis follows the research and development of a prototype chemical and biological sensor based on FBAR FBAR devices were fabricated in a clean room and on die RF measurements were made to identify the units with performance characteristics of high enough quality to be useful as sensors. The FBAR design was then adapted so that it could be environmentally isolated, and microwave circuitry was devised to allow the FBAR to remain in electrical contact with the outside world during its isolation. This allowed for controllable environments in which to test FBAR responses to chemical and biological agents free from interfering signals. A software suite was written to specifically address the requirements for accurate and sensitive data processing of FBAR responses to measured analytes in real time. The isolation assembly and software was tested thoroughly, and the ultimate limits of resolution and sensitivity for the instrumentation were found using temperature change as the variable input parameter. A gas delivery apparatus was constructed and the FBAR was coated with hygroscopic polymer layers to sensitise the device to water vapour. Changes in the concentration of water vapour in a gas stream were tracked and the range of detection was established along with stability and resolution of the chemically sensitised FBAR. FBAR device gold surfaces were coated with biological antibodies, these made the devices ultra specific to measurand. Direct experimental comparisons between the FBAR and the relative performance of well established but lower frequency acoustic wave immunosensor technology systems were made and the relative increase in sensitivity was established for the FBAR based immunosensor. Optical methods were used to compliment the acoustic ones in determining the thickness and density of the protein layers adsorbed to equivalent gold surfaces. The thesis concludes with a section of speculative ideas for future work, with the experimental results for a potential rheological probe device shown. A brief demonstration of the FBAR performance when submerged in semi-infinite liquid environments is shown. Arrays of FBAR devices are software modelled in a novel way and demonstration of their possible applications are presented.